Crescimento e perfil oxidativo de juvenis de Rhamdia quelen alimentados com diferentes níveis de vitamina E (α-tocoferol) na dieta - Uczay, Juliano (2013)
The growth parameters, biochemical, and blood oxidative stress were evaluated in juvenile jundiás fed different levels of vitamin E (0, 200, 300 and 400 mg kg-1 in diet) after 60 days. At the end of the experiment, we observed improvements in growth variables: total length, standard, specific growth rate and condition factor, with the addition of vitamin E in the diet. The erythrocyte count was higher in diets containing vitamin E. The level of 400 mg kg-1 of vitamin E, decreased plasma triglyceride content and increased resistance of erythrocytes. Doses of 300 and 400 mg kg-1, reduced oxidative stress as oxidative biomarkers evaluated in the brain, liver, gills and muscle substances which thiobarbituric acid reactive substances (TBARS), lipid hydroperoxides (LOOH), superoxide dismutase (SOD), catalase (CAT), glutathione-S- transferase (GST) and the content of non-protein thiol groups (NPSH). Doses of vitamin E in the diet of juvenile catfishes above 300 mg kg-1 promotes improvements in growth parameters , and blood antioxidant system .